Protein-templated metal nanoclusters for chemical sensing - Chu, Han-Wei; Demissie, Girum Getachew; Huang, Chih-Ching; Anand, Anisha (Frontiers in Analytical Science, 2025)
Metal nanoclusters (MNCs) possess unique optical properties, discrete energy levels, biocompatibility and photostability, making them pivotal photoluminescent probes in chemical sensing. While substantial work has addressed the synthesis, theoretical studies and applications of gold-, copper-, and silver-based MNCs, this review introduces fresh perspectives on how the nature and concentration of templates—particularly protein molecules—affect the optical properties, stability and sensing capabilities of MNCs. We delve into the merits of using protein templates for creating highly stable MNCs with tunable photoluminescence (PL), providing a detailed comparison with non-protein based systems. This review also unveils recent advancements in the photophysical characteristics and chemical sensing applications of protein-templated MNCs, setting it apart from previous reviews by focusing on cutting-edge innovations in template influence. Challenges and future prospects for protein-templated MNCs in chemical sensing are highlighted, marking critical pathways for upcoming research. This work not only integrates current knowledge but also identifies gaps and opportunities not covered extensively in earlier reviews, such as the nuanced effects of template variation on MNCs’ functional properties.